H3K36 methylation and DNA-binding both promote Ioc4 recruitment and Isw1b remodeler function. Issue 5 (21st February 2022) - Li, Jian; Bergmann, Lena; Rafael de Almeida, Andreia; Webb, Kimberly M; Gogol, Madelaine M; Voigt, Philipp; Liu, Yingfang; Liang, Huanhuan; Smolle, Michaela M
Abstract: The Isw1b chromatin-remodeling complex is specifically recruited to gene bodies to help retain pre-existing histones during transcription by RNA polymerase II. Recruitment is dependent on H3K36 methylation and the Isw1b subunit Ioc4, which contains an N-terminal PWWP domain. Here, we present the crystal structure of the Ioc4-PWWP domain, including a detailed functional characterization of the domain on its own as well as in the context of full-length Ioc4 and the Isw1b remodeler. The Ioc4-PWWP domain preferentially binds H3K36me3-containing nucleosomes. Its ability to bind DNA is required for nucleosome binding. It is also furthered by the unique insertion motif present in Ioc4-PWWP. The ability to bind H3K36me3 and DNA promotes the interaction of full-length Ioc4 with nucleosomes in vitro and they are necessary for its recruitment to gene bodies in vivo . Furthermore, a fully functional Ioc4-PWWP domain promotes efficient remodeling by Isw1b and the maintenance of ordered chromatin in vivo, thereby preventing the production of non-coding RNAs.